Räume des empfindsamen Subjekts. Seelenausfaltungstechnologien in Sénancours „Obermann“ - Steigerwald, Jörn (Epochale Psycheme und Menschenwissen: von Montaigne bis Redonnet)

Ulrike Krieg, Wortbildungsstrategien in der Werbung - Rezat, Sara (Zeitschrift für Sprachwissenschaft 26/1)

Die Konzession als strategisches Sprachspiel - Rezat, Sara

Medialität und Poetik des trompe l ́oeil. W.G. Sebald und Jan Peter Tripp - Öhlschläger, Claudia (Jahrbuch Gegenwartsliteratur. Heft 6/2007: W.G. Sebald)

Ermittlung dynamischer Grenzformänderungsdiagramme für Karosseriestähle - Tröster, Thomas; Berg, J.

Gewalt und Behinderung - Laubenstein, Désirée (Wörterbuch Heilpädagogik)

Director Orientation of Nematic Side-Chain Liquid Crystalline Polymers Under Shear Flow: Comparison of a Flow-Aligning and a Non-Flow-Aligning Polysiloxane - Siebert, Hartmut; Quijada-Garrido, Isabel; Vermant, Jan; Noirez, Laurence; Burghardt, Wesley R.; Schmidt, Claudia (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Knowledge in Action - Hagengruber, Ruth (Computation, Information, Cognition. The Nexus and the Liminal)

Handlungsschemata in der Wissensrepräsentation - Hagengruber, Ruth Edith (presented at the International Conference on Action Types and Knowledge Representation)

Selbstregulierungspotenzial in der Kreditwirtschaft : eine vertragstheoretische und evolutionsökonomische Analyse - Uhde, André

Burgund. Geschichte und Kultur, - Kamp, Hermann

‘You See the Videos But I Know How the Machine Functions’. Human-Robot Interaction and Its Media Representations - Weber, Jutta (Machines as Agency. Artistic Perspectives)

Eine kleine Einführung in die feministische Technowissenschaftsforschung - Weber, Jutta (Kurswechsel. Zeitschrift für gesellschafts-, wirtschafts- und umweltpolitische Analysen. 3/2007)

‚Social‘ Robots & ‚Emotional‘ Software Agents: Gendering Processes and De-Gendering Strategies for ‚Technologies in the Making‘ - Weber, Jutta; Bath, C. (Gender Designs IT. Construction and Deconstruction of Information Society Technology. Studien interdisziplinäre Geschlechterforschung Band 13)

Who’s Afraid of Nature? The Rise and Fall of ‘Denaturalization’ in Contemporary Feminist Thought - Weber, Jutta (Feminist Politics. Identity, Difference, and Agency)

Ethical Regulations on Robotics in Europe - Weber, Jutta; Nagenborg, Michael; Capurro, Rafael; Pingel, Christoph (AI & Society. August 2007)

Interdisziplinäre Kommunikation zwischen den ‚zwei Kulturen' - Weber, Jutta (Journal Netzwerk Frauenforschung NRW Nr. 22/2007)

Simulation mit abstrakten RTOS Modellen in SystemC - Zabel, Henning; Müller, Wolfgang
An komplexe Steuersoftware werden harte Anforderungen bez ̈ug- lich der Einhaltung von Zeitschranken gestellt. Die richtige Wahl eines Echtzeit-Schedulingverfahrens ist hier entscheidend. Die Verwendung von Interrupts in einem Echtzeitsystem erlaubt die zeitnahe Reaktion auf externe Ereignisse. Sie erschwert allerdings die Vorhersagbarkeit von Zeitschranken. In diesem Bericht wird eine Methode zur abstrakten Simulation eines Echtzeitbetriebssystems (Real-Time Operating System/RTOS) in der Systembeschreibungssprache SystemC vorgestellt. Die Verwen- dung eines RTOS-Modelles in SystemC erlaubt die Evaluierung ver- schiedener Schedulingverfahren zu einem fr ̈uhen Zeitpunkt im Ent- wurf des Systems. Interrupts unterliegen allerdings nicht einem RTOS- Schedulingverfahren und m ̈ussen daher gesondert behandelt werden. Dieser Bericht beschreibt die Implementierung eines kanonischen RTOS-Modells zur fr ̈uhen Analyse von Schedulingverfahren, das ei- ne getrennte Modellierung von Task- und Interrupt-Scheduling er- laubt. Dieser Ansatz erlaubt die Trennung des hardwareabh ̈angigen Interrupt-Scheduling in ein separates Modell und eine Evaluierung des Schedules, das sich rein auf Tasks bezieht.

Systematic Testbench Specification for Constrained Randomized Test and Functional Coverage - Krupp, Alexander; Müller, Wolfgang (Proceedings of the 21st European Conference on Modelling and Simulation (ECMS 2007))

TestML - A Test Exchange Language for Model-based Testing of Embedded Software - Großmann, Jürgen; Fey, Ines; Conrad, M.; Wewetzer, Ch.; Müller, Wolfgang (Proceedings of the Automotive Software Workshop '06)

On the Use and Misuse of UML- Application of Diagrams in Engineering - Müller, Wolfgang (Proceedings of the UML for SoC Design Workshop at DAC'07)

Using Smart Cards for Secure and Device Independent User Interfaces - Schäfer, Robbie; Müller, Wolfgang; Marin-López, Andrés; Díaz-Sánchez, Daniel (Proceedings of the International Conference on Mobile Technology, Applications and Systems (Mobility 2007))
Smart Cards are becoming a ubiquitous means for securing a wide range of interactive applications. However in many cases its use is limited for authentication purposes only. In this paper we extend the use of smart cards for carrying abstract user interface descriptions which can be rendered on dierent and potentially remote clients that in addition can support varying interaction modalities. This adds on the one hand to the security since a backend application cannot be used without the UI description, and on the other hand to the versatility of applications, since all devices with a respective renderer for certain modalities can be utilized.

Das Paradigma des Pikaresken - The Paradigm of the Picaresque

Thinking Northern: Textures of Identity in the North of England

The Influence of Catalyst's Oxidation Degree on Carbon Nanotube Growth as a Substrate-Independent Parameter - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Thommen, Verena; Mathys, Daniel (The Journal of Physical Chemistry C)

Optical characterization of alignment and effective refractive index in carbon nanotube films - de los Arcos de Pedro, Maria Teresa; Oelhafen, P; Mathys, D (Nanotechnology)

An Efficient Optical Method to Detect Phase Transitions in Liquid Crystals - Strauß, Jochen; Hoischen, Andreas; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Dual-Frequency Addressable Gratings Based on Polymer-Dispersed Liquid Crystals - Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals Science and Technology. Section A. Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Dichroic photo- and electroluminescence of oligo p-(phenylene vinylene) derivatives - Lauhof, Marcus W.; Benning, Stephan A.; Kitzerow, Heinz-Siegfried; Vill, Volkmar; Scheliga, Felix; Thorn-Csányi, Emma (Synthetic Metals)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Coherent digital polarization diversity receiver for real-time polarization-multiplexed QPSK transmission at 2.8 Gb/s - Pfau, Timo; Peveling, Ralf; Hauden, Jerome; Grossard, Nicolas; Porte, Henri; Achiam, Yaakov; Hoffmann, Sebastian; Ibrahim, Selwan K.; Adamczyk, Olaf; Bhandare, Suhas; Sandel, David; Porrmann, Mario; et al. (IEEE PHOTONICS TECHNOLOGY LETTERS)

PDL-tolerant real-time polarization-multiplexed QPSK transmission with digital coherent polarization diversity receiver - Pfau, T.; Peveling, R.; Hoffinann, S.; Bhandarel, S.; Ibrahim, S.; Sandel, D.; Adamczyk, O.; Porrmann, M.; Noé, Reinhold; Achiam, Y.; Schlieder, D.; Koslovsky, A.; et al. (2007 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Distributed PMD compensator in Lithium-Niobate-Tantalate: Performance Modeling toward highest bit rates - Bhandare, Suhas; Noé, Reinhold (JOURNAL OF LIGHTWAVE TECHNOLOGY)

100 km fiber span in 292 km, 2.38 Tb/s (16 x 160 Gb/s) WDM DQPSK polarization division multiplex transmission experiment without Raman amplification - Abas, Ahmad Fauzi; Hidayat, Ariya; Sandel, David; Milivojevic, Bijana; Noé, Reinhold (OPTICAL FIBER TECHNOLOGY)

Realtime optical synchronous QPSK transmission with DFB lasers - Pfau, T.; Adamezyk, O.; Herath, V.; Peveling, R.; Hoffmann, S.; Porrmann, M.; Noé, Reinhold (2007 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Real-time digital carrier & data recovery for a synchronous optical quadrature phase shift keying transmission system - Noé, Reinhold; Pfau, Timo; Adamczyk, Olaf; Peveling, Ralf; Herath, Vijitha; Hoffmann, Sebastian; Porrmann, Mario; Ibrahim, Selwan K.; Bhandare, Suhas (2007 IEEE/MTT-S INTERNATIONAL MICROWAVE SYMPOSIUM DIGEST, VOLS 1-6)

Liquid crystal director fields in micropores of photonic crystals - Matthias, Heinrich; Schweizer, Stefan L; Wehrspohn, Ralf B; Kitzerow, Heinz-Siegfried (Journal of Optics A: Pure and Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics

Real-time Digital Carrier & Data Recovery for a Synchronous Optical Quadrature Phase Shift Keying Transmission System - Noé, Reinhold; Pfau, Timo; Adamczyk, Olaf; Peveling, Ralf; Herath, Vijitha; Hoffmann, Sebastian; Porrmann, Mario; Ibrahim, Selwan K.; Bhandare, Suhas (2007 IEEE/MTT-S International Microwave Symposium)

Distributed PMD Compensator in Lithium–Niobate–Tantalate: Performance Modeling Toward Highest Bit Rates - Bhandare, Suhas; Noé, Reinhold (Journal of Lightwave Technology)

Coherent Digital Polarization Diversity Receiver for Real-Time Polarization-Multiplexed QPSK Transmission at 2.8 Gb/s - Pfau, Timo; Peveling, Ralf; Hauden, JÉrÔme; Grossard, Nicolas; Porte, Henri; Achiam, Yaakov; Hoffmann, Sebastian; Ibrahim, Selwan K.; Adamczyk, Olaf; Bhandare, Suhas; Sandel, David; Porrmann, Mario; et al. (IEEE Photonics Technology Letters)

Kastrat - Grotjahn, Rebecca (Enzyklopädie der Neuzeit Bd. 6)

Das Elend der Sozialen Arbeit – Die „neue Unterschicht“ und die Schwächung des Sozialen - Heite, Catrin; Klein, Alex; Landhäußer, Sandra; Ziegler, Holger (Erziehung zur Armut? Soziale Arbeit und die ‚neue Unterschicht’)
Die 'neue Unterschicht' ist entdeckt und die Erziehung dieser prekarisierten Gesellschaftsmitglieder wird gefordert. FachexpertInnen aus Erziehungswissenschaft und Sozialpädagogik gehen in diesem Band der Frage nach, wie angemessen eine solche Diagnose der 'neuen Unterschicht' und der damit verbundene Therapievorschlag einer Erziehung zur Armut ist: Wie wird hier soziale Ungleichheit in einer veränderten Form zum Gegenstand? Welche Herausforderungen sind damit für die Soziale Arbeit verbunden? Hält die Diagnose einer 'neuen Unterschicht' einer empirischen Überprüfung stand? In welcher Weise werden hier bestimmte Bevölkerungsgruppen zum Zielpunkt politischer Strategien? Die Beantwortung dieser Fragen macht das Spannungsverhältnis struktureller, kultureller und moralischer Erklärungsversuche mit Blick auf eine fachliche und politische Verortung Sozialer Arbeit analysierbar.
Keywords: Bildung Gesellschaft Moral Soziale Arbeit Sozialpädagogik Sozialstaat Unterschicht neue Unterschicht

"Antlitz der Zeit". Zur soziologisch-politischen Dimension des Physiognomischen in der Ära der Neuen Sachlichkeit - Öhlschläger, Claudia (Die Souveränität der Literatur. Zum Totalitären der Klassischen Moderne 1900-1933)

Middleware for Secure Home Access and Control - Marin, Andres; Müller, Wolfgang; Schäfer, Robbie; Almenarez, Florina; Diaz, Daniel; Ziegler, Max (Proc. of the IEEE PerCom Middleware Support for Pervasive Computing (PerWare 2007))
User adaptive systems in the context of pervasive computing can only unveil their power if based on a generic middleware managing private data and context information in combination with flexible device access and control. However, managing those data poses severe privacy problems both legally and from a trust perspective. Therefore we propose a home automation middleware for secure management of user and context data that gives access to services just for the authorized users and devices. The middleware has been successfully tested at the ambient computing (AC-LAB) at the University of Paderborn.

Device Independent User Interfaces for Smart Cards - Schäfer, Robbie; Müller, Wolfgang; Marin-López, Andrés; Díaz-Sánchez, Daniel (Proceedings of the 9th International Conference on Human Computer Interaction with Mobile Devices and Services (MobileHCI2007))
Smart Cards are becoming a ubiquitous means for securing a wide range of interactive applications. However in many cases its use is limited for authentication purposes only. In this paper we extend the use of smart cards for carrying abstract user interface descriptions which can be rendered on different and potentially remote clients that in addition can support different interaction modalities. This adds on the one hand to the security since a backend application cannot be used without the UI description, and on the other hand to the versatility of applications, since all devices with a respective renderer for certain modalities can be utilized.
Keywords: Smart Card; Abstract User Interface; Device Independence

A Low-Cost Positioning System for Location-Aware Applications in Smart Homes - Schäfer, Robbie; Müller, Wolfgang; Deimann, Roman; Kleinjohann, Bernd (Proceedings of the Workshop on Mobile Spatial Interaction at CHI 2007)
Location-aware services for private use such as GPS- based navigation systems and GSM-based offerings have become quite a success for outdoor applications, while indoor positioning systems are still mainly employed for professional use only. The main reasons are cost issues and the complexity of setup and maintenance of those systems. In this paper we present CaMPTrack (Camera-based Multiple Person Tracker), a prototype of a webcam-based positioning system and discuss its application and development challenges.
Keywords: Positioning Systems; Camera Based; Cost Efficiency; Smart Home Applications

Evaluation of a Multimodal System Based on Dialogue Models and Transformations International Workshop on Usability of User Interfaces: From Monomodal to Multimodal - Schäfer, Robbie; Müller, Wolfgang (Proceedings of IWUMUI’2007 at HCI'2007)

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Optoelectronic and photonic properties of liquid crystals: electroluminescence and photorefractivity - Benning, Stephan A.; Lauhof, Marcus W.; Paelke, Lutz; Redler, Andreas; Scheliga, Felix; Thorn-Csanyi, Emma; Vill, Volkmar; Kitzerow, Heinz-Siegfried (SPIE Proceedings)

Stabilization of bi‐linear mixed finite elements for tetrahedra with enhanced interpolation using volume and area bubble functions - Mahnken, Rolf; Caylak, Ismail (International Journal for Numerical Methods in Engineering)